Explanatory models of psychotic-like experiences in rural Burkina Faso: A qualitative study among indigents and their community - Émilie Pigeon-Gagné; Teodora Vigu; Kadidiatou Kadio; Emmanuel Bonnet; Valéry Ridde (Elsevier, 2022)
Background: In Sub-Saharan Africa, psychiatric care for severe mental disorders is scarce. This is especially true for people living in chronic poverty in rural areas. The way in which people with psychotic manifestations are socially perceived and treated remains under-researched, limiting the possibility of adapting services to their needs. Methods: In May 2017, 29 semi-structured individual interviews with indigent people reporting psychotic-like experiences and 8 focus groups with members of their community were conducted in the rural region of Diébougou (Burkina Faso). Indigents were questioned on their subjective interpretation regarding these experiences. Community members were asked about their perceptions of people manifesting psychotic-like experiences. A thematic analysis was carried out. Results: Three distinct conceptions of psychotic-like experiences were identified. First, these experiences were often understood as a reflection of a mental disorder involving evil supernatural entities. Second, some people were considered as possessing a faculty that conferred supernatural powers that could be used for healing purposes. Finally, psychotic-like experiences might also reflect a temporary disturbance for which no significant repercussions were raised. Conclusions: This study suggests that certain manifestations qualified as psychotic according to the biomedical nosology seem to be considered differently from communities' perspectives. These experiences were frequently interpreted as being personal and not requiring medical attention or even as socially valuable faculties. Although psychotic-like experiences were not always perceived negatively, people who experienced them were reluctant to talk about them. This suggests that a form of stigmatization is associated with psychotic-like experiences.